2007
DOI: 10.1300/j461v03n04_04
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Australian Heterosexuals Toward Same-Sex Parents

Abstract: This is the first study of attitudes of Australian heterosexuals toward heterosexual, gay male, and lesbian parents and the children raised by these parents. A sample of Australian heterosexual males and females read one of six vignettes describing a family situation. Participants assessed the parents' emotional stability, responsibility, and competence; Charmaine Morse, MAppSci, is a psychologist employed at a psychiatric clinic in regional Victoria, Australia.Suzanne McLaren, PhD, is Senior Lecturer in Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 63 publications
(95 reference statements)
6
38
1
6
Order By: Relevance
“…In 1998, this was the case for somewhat more than half the sample, but a larger proportion then reported that they were explicitly concerned as opposed to not taking a stand or being uncertain (MMI 1998). Population concerns in relation to lesbian and gay parenthood are also reported in earlier studies from other countries (Crawford and Solliday 1996;King 2001;McLeod et al 1999;Morse et al 2008).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In 1998, this was the case for somewhat more than half the sample, but a larger proportion then reported that they were explicitly concerned as opposed to not taking a stand or being uncertain (MMI 1998). Population concerns in relation to lesbian and gay parenthood are also reported in earlier studies from other countries (Crawford and Solliday 1996;King 2001;McLeod et al 1999;Morse et al 2008).…”
Section: Discussionsupporting
confidence: 69%
“…The fact that beliefs about same-sex marriage rights, lesbian and gay parenthood and beliefs about the welfare of children with lesbian and gay parents at large are predicted by the same demographic variables, including religion and political affiliation, is supported by earlier findings (e.g. Brumbaugh et al 2008;EOS Gallup Europe 2003;Pearl and Galupo 2007;Morse et al, 2008). Research on population attitudes towards lesbian and gay parenting further suggests that negative attitudes are associated with antigay attitudes and sexual prejudice (Crawford and Solliday 1996;Morse et al 2008).…”
Section: mentioning
confidence: 72%
See 2 more Smart Citations
“…Professionals working with families in different contexts as well as heterosexually identified lay people have been interviewed and surveyed about their attitudes towards or reflections on same-sex parenting (e.g. Averett & Hegde, 2012;Becker & Todd, 2013;Chapman, Watkins, Zappia, Combs & Shields, 2012;Choi, Thul, Berenhaut, Suerken & Norris, 2006;Spidsberg & Sørlie 2012;Hegde, Averett, Parker White & Deese, 2013;Herbstrith, Tobin, Hesson-McInnis, & Schneider, 2013;Hollekim et al 2012;Morse, McLaren & McLachlan, 2007;Nicol, Chapman, Watkins, Young & Shields, 2013). Policy documents and juridical decisions may also serve as valuable data sources (e.g.…”
Section: Limitationsmentioning
confidence: 99%